Experience of state regulation of the production and circulation of dietary supplements in Ukraine (Environment & Health, 2025)
The purpose of the work. To determine the successive stages of legislative regulation of the production and circulation of dietary supplements In Ukrainian, to identify the main shortcomings and directions for further improvement of this process.Materials and methods. Analysis of legislative and regulatory acts of the national and European level on issues of regulating the production and circulation of dietary supplements In Ukrainian. The analysis was carried out using retrospective-analytical, bibliographic, system-structural methods and the method of informal (traditional) analysis.Research results. Based on the generalization of legislative and regulatory legal acts of the national and international levels, the main stages and their shortcomings in solving the problem of regulating the production and circulation of dietary supplements In Ukrainian were identified. It has been established that this process can be divided into 4 stages: problem identification, accumulation of initial experience and attempts to regulate the circulation of dietary supplements (mid-90s to 2004); integration into EU legislation to ensure legal adaptation of Ukrainian legislation to EU requirements (2004–2015); unification of Ukrainian and European norms aimed exclusively at controlling the production and circulation of dietary supplements and deregulation of the food market, including dietary supplements (2015–2024); from 2025, a new stage of regulating the production and circulation of dietary supplements begins in accordance with the Law of Ukraine №4122-IX «On Amendments to Certain Laws of Ukraine on Improving the Regulation of the Production and Circulation of Dietary Supplements, and on Regulating Other Issues in the Sphere of Healthcare». It has been determined that this Law does not fully correspond to modern realities and has a number of unregulated provisions regarding activities of operators of the dietary supplements market In Ukrainian. „ Conclusions. It has been established that the Law of Ukraine «On Amendments to Certain Laws of Ukraine on Improving the Regulation of the Production and Circulation of Dietary Supplements, and on Regulating Other Issues in the Sphere of Healthcare» does not contain effective mechanisms for regulating the production and circulation of dietary supplements on the Ukrainian market. The implementation of the Law requires the development of subordinate regulatory documents that would determine the research algorithm and create clear mechanisms for introducing DD into circulation. At the notification stage, it is necessary to ensure a harmonized scientific and evidence based assessment of the safety of DD, which should be carried out by scientific institutions with a profile of research on food safety. To confirm the scientific evidence base regarding the quality and safety for the population of dietary supplements at the stage of their notification, there is an urgent need to create an inter-sectoral permanent commission with the involvement of relevant representatives of the Ministry of Health of Ukraine, the State Service for Food and Consumer Protection, public organizations and mandatory scientific support.
Keywords: biologically active supplement (BAA); dietary supplement (DS); regulation of production and circulation of DD; Law of Ukraine; regulatory legal acts; Order of the Ministry of Health of Ukraine; EU Directive; EU Regulation